Representasi Multilingualisme Penanda Sarana Pariwisata di Kawasan Wisata Canggu - Savitri, Putu Weddha (Humanis, 2021)
This paper, as part of the study of Landscape Liguistics, aims to reveal how the multilingualism is represented in the public space in this area. In addition, to find out how the structure of writing and language patterns used in public spaces in the area. To collect the data, the method used in this research is the documentation method, then the data was analyzed quantitatively and qualitatively. The results showed that there were 13 languages ??used in public spaces, especially on markers of existing tourism facilities. English is the most dominant language used, Latin writing is also used in almost all markers, and also the language pattern that uses 2 - 3 different languages ??has shown this area to be considered as an international region.